2017
DOI: 10.5511/plantbiotechnology.17.0326a
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of rice sucrose synthase isoforms promotes the activity of sucrose degradation

Abstract: Sucrose is utilized as an initial material for production of the storage substances. Sucrose synthase reversibly catalyzes reactions of the sucrose degradation and its synthesis between sucrose with UDP and UDP-glucose with fructose. They also had the activity of the reactions for sucrose degradation of sucrose with ADP, and sucrose synthesis from ADPglucose and fructose. Rice has three representative isoforms of sucrose synthase, Rsus1, Rsus2, and Rsus3, in which Rsus1 and Rsus3 are highly expressed in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The second site is also a serine, at around position 170, and is thought to regulate protein degradation (Hardin et al, 2003). In vitro phosphorylation of rice SuSy proteins, Rsus1-3 may promote SuSy activity (Takeda et al, 2017).…”
Section: Structure and Enzymatic Activity Of Susymentioning
confidence: 99%
“…The second site is also a serine, at around position 170, and is thought to regulate protein degradation (Hardin et al, 2003). In vitro phosphorylation of rice SuSy proteins, Rsus1-3 may promote SuSy activity (Takeda et al, 2017).…”
Section: Structure and Enzymatic Activity Of Susymentioning
confidence: 99%
“…In maize, phosphorylation of the amino terminal portion of SuSy determines the association of the protein with different cell compartments [ 62 ], as well as in tomato fruit [ 68 ]. As already stated, the phosphorylation of SuSy can also affect its enzymatic activity, for example in relation to the synthesis of callose [ 69 ] or to the increased degradation of sucrose [ 70 ]. In other cases, phosphorylation in distinct amino acid residues may be a signal for the proteolytic degradation of the enzyme [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acidic pH (in the range of 5.5 - 7.5) has been shown to promote cleavage activity, whereas pH in the range of 7.5 - 9.5 promotes the synthesis activity of the enzyme (Schmolzer et al, 2016; Stein and Granot, 2019). SUS activity also depends on the carbohydrate status, particularly on sucrose metabolism (Takeda et al, 2017). As discussed earlier, a higher amount of sucrose reaching the stem of O. australiensis accumulated in the apoplasm, due to sucrose transporters and lower cell wall invertase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to O. australiensis , higher synthesis activity of SUS in the Nipponbare stem might contribute to the sucrose synthesis to be mobilized for grain filling at the heading stage. The differences between the synthesis and cleavage activities of SUS between the two species could be due to many potential factors, such as pH and metabolic status of the tissue, cellular localization, phosphorylation, and oligomerization status of the enzyme (Schmolzer et al , 2016; Stein and Granot, 2019; Takeda et al , 2017). Our results on differential activity of cell wall invertase and starch levels in the stem suggested that the metabolic status of the stem could likely be an important determinant for the differences in synthesis and cleavage activity of SUS between the two species.…”
Section: Discussionmentioning
confidence: 99%